2020
DOI: 10.1177/2397198320925684
|View full text |Cite
|
Sign up to set email alerts
|

Comparing paediatric- and adult-onset linear morphoea in a large tertiary-referral scleroderma centre

Abstract: Background: Linear morphoea is a severe morphoea subtype associated with extracutaneous manifestations, potentially permanent disfigurement and functional impairment. Linear morphoea is more prevalent in paediatric patients, and knowledge of disease in adults is limited. The objective of this study was to compare paediatric- and adult-onset linear morphoea, in an exclusively adult population. Methodology: This was a retrospective cohort study of adult patients with linear morphoea seen over a 3-year period at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 29 publications
(41 reference statements)
0
21
1
Order By: Relevance
“…Pediatric‐onset JLS was noted to have 2.6 odds of active disease compared with adult‐onset disease, with notable differences between damage scores (LoSDI 19.5 > 8.1). In this study, univariate analysis showed that children are at a higher risk of ongoing active disease, more cumulative damage, and potentially increased functional impairment 23 . In this cohort, 56.3% escalated therapy, and a third of these required more than one immunosuppressive agent.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…Pediatric‐onset JLS was noted to have 2.6 odds of active disease compared with adult‐onset disease, with notable differences between damage scores (LoSDI 19.5 > 8.1). In this study, univariate analysis showed that children are at a higher risk of ongoing active disease, more cumulative damage, and potentially increased functional impairment 23 . In this cohort, 56.3% escalated therapy, and a third of these required more than one immunosuppressive agent.…”
Section: Discussionmentioning
confidence: 59%
“…In this study, univariate analysis showed that children are at a higher risk of ongoing active disease, more cumulative damage, and potentially increased functional impairment. 23 In this cohort, 56.3% escalated therapy, and a third of these required more than one immunosuppressive agent. These medications, as discussed below, add negatively to the patient and caregiver experience.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations